Cross mapping of self-care interventions for expert patients - dos Santos Bezerril, Manacés; Barreto Tavares Chiavone, Flávia; Cunha da Silva, Larissa Arielly; Fernandes Costa, Isabelle Katherinne; Sánchez Ayllón, Francisca; Vázquez Santiago, Maria Soledad; Campos de Azevedo, Isabelle; Pereira Santos, Viviane Euzébia (Investigación y Educación en Enfermería, 2024)
Objective. To compare the primary nursing interventions described in the literature to promote self-care among expert patients with the Nursing Interventions Classification. Methods. This descriptive and exploratory study used a quantitative approach and cross-mapping focusing on 23 self-care actions obtained from a scoping review conducted in January 2022 in Brazilian and international databases. Data were descriptively analyzed, processed, and presented in tables. Results. Twenty-three self-care actions were found in the scoping review. A total of 56 interventions were selected, 30 of which were associated with self-care actions; some were associated with more than one intervention (e.g., physical activity, avoiding alcohol consumption, blood glucose monitoring, blood sugar management, stress/anxiety). Conclusion. The self-care interventions promoted among expert patients were compared to the Nursing Interventions Classification, enabling nurses to lead by encouraging, assisting, teaching, discussing, and guiding patients. Hence, nursing workers can improve their work process by encouraging patient self-care and autonomy in the health-illness continuum.